"Some fuzzy math": relational information on debt value adjustments by managers and the financial press - Sebastian Kaumanns (Business Research, 2019)
This study provides comprehensive descriptive evidence on the occurrence, size, and reporting by managers and the financial press of debt value adjustments due to a change in own credit risk (DVAs). The study is motivated by a public debate about DVAs in which critics describe them as 'counterintuitive' and claim that managers disclose DVA information strategically to make firms 'look good'. Analyzing a sample of 405 firm-quarters of 19 US financial firms that report DVAs between 2007 and 2014, I found that positive and negative DVAs appear similarly often and with similar magnitude. I further found that managers provide more information on large negative DVAs compared to positive DVAs. Managers also provide more DVA information when they have strategic incentives to do so. Examining newspaper articles on 202 firm-quarters, I found that the financial press is more likely to cover large positive DVAs and DVAs about which managers provided more information. Analyzing the articles' content, I found that the press is more likely to provide new DVA information if managers' press releases contain little information. The findings are in line with popular claims of asymmetric DVA reporting by managers. They are further consistent with the financial press acting as a counterweight to such asymmetric reporting.
Keywords: G21; M41; 650; Fair value option; Debt value adjustments; Own credit risk; ASC 825; Financial instruments